Site-specific one-pot triple click labeling for DNA and RNA - Winz, Marie-Luise; Jäschke, Andres (Chemical communications, 2018)
We report site-specific triple click labeling for DNA and RNA in a one-pot setup by performing inverse electron demand Diels-Alder reaction and strain-promoted and copper catalyzed click reactions sequentially. Our methodology can be applied to long and short nucleic acids alike, and could have broader potential for labeling other (bio-)molecules.
Gesehen am 31.03.2020